PENGARUH CONTENT MARKETING, INFLUENCER, DAN FREE ONGKIR TERHADAP MINAT BELI KONSUMEN PRODUK FASHION PADA TIKTOKSHOP - Pratiwi, Duwi; Hermawati, Ati; Kurniawati, Dewi (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2023)
ABSTRACT This study consists of four variables, namely content marketing as the independent variable (X1), influencer as the independent variable (X2), free shipping as the independent variable (X3), while the dependent variable is consumer buying interest (Y). The population in this study is the number of users of the TikTok application in the Depok area is unknown. The data source used is primary data. The sampling technique used was purposive sampling method using the ancient roa formula so that it can be concluded that the sample in this study was 100 people. The final results of the study concluded that 1) content marketing has a positive and significant effect on consumer buying interest 2) influencers have a positive and significant effect on consumer buying interest 3) free shipping has a positive and significant effect on consumer buying interest 4) content marketing, influencers , and free shipping has a positive and significant effect on consumer buying interest . Keywords: Content Marketing, Influencers, Free Shipping, Consumer Purchase Interest